Teaching Genres to Advanced Learners - Tincheva, Nelly (Baltic Journal of English Language, Literature and Culture, 2016)
The paper reflects recent thinking and research on what genre is, what the purposes of teaching genres are, and how genres should be taught. The paper argues a case for the application of prototype theory to teaching genres, especially with a view of teaching genres to advanced learners. To align its method with the objective specified, the paper presents perception-based data from questionnaire responses provided by a study group of 100 University students. Results from a test on both the receptive and productive skills of the respondents in the group are discussed. Final Test results of the experimental group and a control group are contrasted. The general method applied is a quantitative one as it coheres with the basic postulates of Rosch’s experimental prototype theory. The research method applied is experiment. The conclusions drawn from the study’s data corroborate strongly the applicability of the notion of prototypes to genre teaching.